2018
DOI: 10.1016/j.clinthera.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Treatments for Previously Treated Multiple Myeloma: A Systematic Literature Review and Network Meta-analysis

Abstract: This NMA provides comparative efficacy for MM treatments not studied in head-to-head RCTs. The NMA suggests that, compared with other approved MM treatments in the United States, DRd and DVd have a higher probability of providing the longest PFS in patients who have received at least 1 prior therapy and in patients who have received only 1 prior therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 50 publications
1
32
0
1
Order By: Relevance
“…In their network metanalysis of results from the ELOQUENT-2 (Elo-Rd) and POLLUX (DRd) trials, Dimopoulos et al calculated an HR of 0.54 for PFS and 0.82 for OS, indicating that the POLLUX regimen is statistically the most efficacious of the two [51]. This was like the HR value of 0.59 computed for PFS by Maiese et al in their comparison of the same two trials [53]. Finally, Beurden-Tan et al found that Elo-Rd ranked third as the best possible treatment among 18 salvage therapeutic options (four including a MoAb) [52].…”
Section: Metanalyses Of Elotuzumab Combinationsmentioning
confidence: 77%
See 1 more Smart Citation
“…In their network metanalysis of results from the ELOQUENT-2 (Elo-Rd) and POLLUX (DRd) trials, Dimopoulos et al calculated an HR of 0.54 for PFS and 0.82 for OS, indicating that the POLLUX regimen is statistically the most efficacious of the two [51]. This was like the HR value of 0.59 computed for PFS by Maiese et al in their comparison of the same two trials [53]. Finally, Beurden-Tan et al found that Elo-Rd ranked third as the best possible treatment among 18 salvage therapeutic options (four including a MoAb) [52].…”
Section: Metanalyses Of Elotuzumab Combinationsmentioning
confidence: 77%
“…Of note, DRd reduced the risk of progression or death by 81% versus bortezomib plus dexamethasone, and 63% versus lenalidomide plus dexamethasone. Finally, Maiese et al published a meta-analysis of 27 trials in which they concluded that DRd and DVd were comparatively efficacious in terms of both significantly higher ORR and lower risk of progression or death, with a higher probability of providing the longest PFS in patients who have received only 1 prior therapy [53].…”
Section: Meta-analyses Of Daratumumab Combinationsmentioning
confidence: 99%
“…The introduction of several novel agents and targeted therapies over the last 10 years has revolutionized the management of MM and has produced unprecedented outcomes in terms of disease control and OS. Currently, novel agents and targeted therapies are used in the following settings: (1) prior to HSCT to reduce tumor burden and to optimally control MM, (2) following HSCT as consolidation and maintenance therapy to allow long-term disease control and (3) as salvage therapy in case of relapse of MM after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma (MM) is an incurable, debilitating and heterogeneous malignancy that has highly variable clinical course [1][2][3][4][5][6]. It is a plasma cell neoplasm characterized by neoplastic proliferation of a single clone of plasma cells in the bone marrow (BM) producing a monoclonal immunoglobulin and causing anemia, renal failure, bone destruction and infectious complications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation